PENDAMPINGAN ORIENTASI KRITIK HADIS MISOGINIS TENTANG KURANGNYA AKAL PEREMPUAN DALAM PENAFSIRAN IBNU KATSIR QS. AL-BAQARAH: 282 DI MAJLIS TA’LIM MASJID AN-NUR, BABELAN BEKASI - Salman Faris; Aulia Sholihah; Kholilurrohman Kholilurrohman; Muhamad Zaenal Arifin; Andi Rahman; Muhsin Muhsin (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
At the same time as respect for the status and dignity of women is growing, several hadiths are misunderstood as misogynistic hadiths that demean women. Among the misunderstood hadiths is the hadith which states that women are less intelligent. This hadith in Ibn Kathir's book is used as an interpretation of the QS. Al-Baqarah 282 regarding testimony. So this increasingly gives rise to readers' belief that female creatures are creatures that are less intelligent than male creatures. This article wants to clear up this misunderstanding by explaining the correct understanding of this hadith, by analyzing it textually and contextually